The strengthening of resin cemented dental ceramic materials - Hooi, Paul (Trinity College (Dublin, Ireland). School of Dental Science, 2013)
The aim of the current investigation was to advance the understanding of the mechanism of resin-strengthening conferred to dental ceramic materials by resin-based composite materials. The investigation is presented as a series of manuscripts. In the first study (Manuscript 3.1), dental porcelain disc-shaped specimens were resin-coated with three resin-based composite materials with different flexural moduli at discrete resin thicknesses. The discs were loaded to failure in a biaxial flexure test and the maximum tensile stress calculated with an analytical solution to determine the magnitude of resin-strengthening. Linear regression techniques were utilised to identify the theoretical strengthening at a 'zero' resin-coating thickness. A finite element analysis model was employed to verify the analytical solution and validate the experimental data. The tlexural modulus and thickness of the resin-based composite materials were observed to have a significant impact on the magnitude of resin-strengthening. A soda lime glass analogue material for dental porcelain was identified to reduce the variability associated with specimen preparation (Manuscript 3.2). The study examined the influence of pre-cementation operative variables (alumina particle air abrasion and HF acid-etching) and resin-cement coating on the biaxial flexure strength of the soda lime glass analogue for dental porcelain. The soda lime glass analogue demonstrated the same patterns of strength dependence influenced by pre-cementation parameters and resin-cementation variables characterised previously for dental porcelain. Load to failure testing of dental ceramic materials is typically performed at a constant standardised testing rate.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin